Apoyo en supervisión de obra en el desarrollo de proyectos de la constructora El Tikal en Duitama, Boyacá (2022)
The development of this internship consisted in a general way of accompanying the resident engineer, executing the supervision of the works in the construction stage of multifamily projects; to be more precise, the “campos multifamily housing” project; The methodology of this internship is of a mixed type, since most of the activities were based on the supervision and accompaniment on site, without neglecting the activities that are of a documentary nature. On the part of the intern, certain calculation documents were offered regarding the necessary reserve tanks, on the other hand in the works, would verify the correct execution of the activities. about areas, angles and other factors that This document validates what was previously described through photographic records and descriptions of these activities.